Lateral orbitotomy for treatment of an orbital abscess in a dog. (7th May 2014) - Vallefuoco, R.; Molas, C.; Moissonnier, P.; Chahory, S.
<x xml:space="preserve">Abstract</x> A two‐year‐old Jack Russell terrier was diagnosed with a retrobulbar abscess and orbital cellulitis. The diagnosis was confirmed by ultrasound, magnetic resonance imaging examination and ultrasound‐guided fine‐needle aspiration. Transoral ventral drainage was attempted but was unsuccessful. The abscess was successfully treated by open drainage through a lateral orbitotomy. Despite the exposure of the orbital structures, the orbital soft tissues healed by second intention without further complications. The open drainage was well tolerated and resulted in immediate reduction of inflammation and pain, allowing a quick recovery. This report describes the diagnosis and, surgical management and the long‐term (3 years) follow‐up of an unusual case of orbital abscess associated with diffuse periorbital cellulitis successfully treated by open drainage through a lateral orbitotomy.